Evaluation Of Children's Nutritional Status With Beta Thalassemia Major Based On BMI (Journal of Pharmaceutical Negative Results, 2022)
Background: The severe anemia that characterizes beta thalassemia major is a genetic blood condition. Children who have this illness often struggle with their diet. To better understand and meet their nutritional requirements, this research will use BMI classification based on WHO guidelines to evaluate their nutritional status.Objective: To evaluate the children with significant thalassemia's nutritional condition using the WHO-based BMI categorization system at the Pediatric department of MMC MardanStudy Design: A Cross-sectional studyPlace and Duration of Study: This study was conducted at the pediatric department of MMC Mardan from Jan 2020 to Dec 2020Materials and Methods: Children with Thalassemia major who visited the pediatric department or Thalassemia unit between the ages of 0 and 215 months were included by successive non-probability sampling. After determining their height and weight, the BMI was computed. The nutritional status of 0-60 months old children was classified according to BMI based WHO classification for 0-60 months age group as obese, overweight, regular, moderate acute malnutrition (wasting), and severe acute malnutrition (severe wasting), while the nutritional status for 59-212 months old children was classified according to BMI based WHO classification for 5-19 years age group as obese, overweight, normal, thin and severely thin.Results: There were 165 cases in all, ranging in age from 0 to 212 months, and 81 (54%) of them were male. 84 (56.22%) of the 70 cases in the 0-60 month age group were male. In the 'normal' BMI categorization group, there were 39 (55%) instances; of these, 22 (54.22%) were male, and 17 (55.74%) were female (p-value 0.8190). In the category of 60–215 months old, there were 80 instances; 43 (53.12%) of them were male. Twenty-six cases (16.5%) fell into the BMI categorization group labeled as "normal," of which 12 cases 16 were female and 14 cases (16.94) were male (p-value 0.8991).Conclusion: Children with thalassemia major often have undernutrition, which becomes worse as they get older, regardless of gender.